Structural and Biochemical Studies on Novel Bacterial Haem-Proteins - Schneider, Sabine (2007)
Haem proteins are functionally and structurally extremely diverse biomolecules and play a vital role in aerobic life. They perform a vast range of functions like transport of oxygen and electron transfer, gene regulation, redox-sensing and drug metabolism. This many-sidedness of haem-proteins is due to the extremely versatile chemical properties of the iron in the haem prosthetic group. Iron, or iron in the form of haem, plays a key role in many biological processes and it is an essential nutrient for the majority of living organisms. Despite being one of the most abundant chemical elements, iron is scarcely available under physiological conditions, because of its insolubility and toxicity. Pathogenic bacteria rely on their host as a source of haem and/or iron and a strong link between iron / haem acquisition, virulence factors and pathogenicity exists. Therefore they have evolved a set of specialised haem receptors and carriers to circumvent their iron dependency, often involving the 'stealing' of haem as a source of iron from host's haem-proteins, which in the host is the most abundant and relatively available source of iron. These proteins are both vital and unique to bacteria and so have been considered as possible drug targets. At the beginning of this thesis work, the fascinating cell and molecular biology mechanisms of these novel haem binding proteins were still largely unexplored. In this thesis the cloning, expression, purification of four novel bacterial haem transport proteins for biochemical and biophysical characterisation and structural studies is described: HemS and HemT from Yersinia enterocolitica and Shp and HtsA from Streptococcus pyogenes. HtsA in complex with haem was crystallised and a preliminary X-ray diffraction analysis was carried out. Furthermore HemS was crystallised in its apo- and haem bound form and both structures were determined. Comparison of the apo- and haem-bound crystal structures provide penetrating insights into its mechanism of haem binding and release.